Pengembangan Bahan Ajar Matematika Bisnis Berbasis Komputer Untuk Mahasiswa Jurusan Akuntansi Politeknik Negeri Bali - I Made Wijana; Anak Agung Putri Suardani; I Gede Made Karma (Epigram, 2019)
This research aims to produce prototype of computer-based business mathematics teaching materials to improve student achievement of Accounting Department, Politeknik Negeri Bali (PNB). In this research, to reach the target of teaching materials of computer-based business mathematics, the development using Borg and Gall method with some modifications into five steps: needs analysis and curriculum majoring in accounting, initial product development, education expert validation, small group trial , and large group trials. Trial of small group and large group by involving first semester student of Diploma IV Managerial Accounting Study Program, Accounting Department, PNB. Based on curriculum analysis and needs analysis, teaching materials are developed in the form of modules with Microsoft Excel application and the result of the initial product are five modules with topics of Formula, Linear and Non Linear Functions, Interest Calculation, Annuity, and Linear Programming. Education expert validation using five aspects resulted in an average score of 4.13 (good). Trial of the teaching materials by measuring student perceptions using three aspects for small groups resulted in an average score of 3.81 (good) and for large groups resulted in an average score of 4.23 (good). Furthermore, results of evaluation in large groups indicate a significant increase in mean of student scores from before and after using computer-based Business Mathematics teaching materials